2011
DOI: 10.1136/bcr.03.2011.3953
|View full text |Cite
|
Sign up to set email alerts
|

Acute myocardial infarction caused by paradoxical embolism with concomitant pulmonary embolism

Abstract: An 86-year-old lady presented with an acute inferior ST elevation myocardial infarction. The coronary angiogram showed a thrombotic occlusion of the right coronary artery, which was aspirated, but there was no underlying lesion to stent. The patient remained very hypoxic on the ward with clear lung fields and was found to also have multiple pulmonary emboli on CT pulmonary angiogram. Paradoxical embolism was suspected as the cause of myocardial infarction and subsequent echocardiography studies indeed confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Such cases accounted for only 2.9% of the referrals to a specialised centre for the evaluation of PFO 5. Such diverse and relatively rarer presentations include acute limb ischaemia,4 6 7 renal infarction,8 9 ischaemia of the digestive tract10 and also myocardial infarction 11 12. Knobloch et al 13 reported a similar case in a young man with myocardial infarction, popliteal artery occlusion and carotid thrombus.…”
Section: Discussionmentioning
confidence: 99%
“…Such cases accounted for only 2.9% of the referrals to a specialised centre for the evaluation of PFO 5. Such diverse and relatively rarer presentations include acute limb ischaemia,4 6 7 renal infarction,8 9 ischaemia of the digestive tract10 and also myocardial infarction 11 12. Knobloch et al 13 reported a similar case in a young man with myocardial infarction, popliteal artery occlusion and carotid thrombus.…”
Section: Discussionmentioning
confidence: 99%
“…5,9 These included at least 17 presumed cases of paradoxical coronary embolism, diagnosed post mortem, of which at least five occurred simultaneously with diagnosed pulmonary embolism. [10][11][12][13][14][15] It has been recently suggested that myocardial infarction resulting from paradoxical coronary embolism may be under-diagnosed, in patients with pulmonary embolism a patent foramen ovale. 5 Coronary embolisms have in autopsy series been reported to lodge distally and occur 3-4-times more often in the left than the right coronary artery.…”
Section: Discussionmentioning
confidence: 99%
“…Three cases of successful thrombus aspiration for paradoxical coronary emboli without stenting have been reported previously. [11][12][13] While dual antiplatelet therapy is central in the prevention of stent thrombosis and secondary prevention after myocardial infarction, the current standard in secondary prevention of pulmonary embolism is anticoagulation with warfarin 17 or administration of the novel oral anticoagulants. 18 This is problematic since the combined use of dual antiplatelet therapy and oral anticoagulation (triple antithrombotic therapy), confers substantial risk of bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…The embolisms have preference to be transmitted primarily into the cerebral arteries and there to the posterior vessels [ 2 ]. But we also found a subset of patients with MI caused by this pathophysiology, and associations with thrombophilia, pulmonary embolism (PE) and stroke have been reported [ 5 7 ]. Most cases described in literature are presumed with no evidence of actual transit of thrombus across a left-right intracardiac shunt.…”
Section: Discussionmentioning
confidence: 64%